Competency Rating of Soils for Civil Engineering Structures Around Southern Rayfield, Jos, Plateau State, North Central Nigeria - Isaac Edimeh , Abalaka; Ilemona, Amos (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Competency ratings of soils around Southern Rayfield were carried out in other to determine their competent ratings for civil engineering structures. The engineering tests carried out includes : Sieve analysis, Atterberg limits and compaction tests. Sieve analysis result showed that the incompetent soil samples had a range of 49 – 58 % of the soil passing through sieve no 200 which are fine materials (clay). The competent soil samples had a range of 25 – 35 % passing through sieve no 200 indicating the dominance of sand / gravel in the area. For Atterberg Limit test, the plasticity index for the soil samples that are incompetent had a range of 25 – 35 % which implies high swelling potential indicative of clay while soil samples gotten from the competent areas had a range of 15.5 – 18.4 % which indicates low swelling potential and are basically sand / gravel. For compaction, competent soil samples had maximum dry density range of 1.83 – 1.87 % and optimum moisture contents had a range of 12.3 – 14.3 %. The incompetent soil samples maximum dry density range of 1.67 – 1.84 % while their optimum moisture contents had a range of 16.2 – 26.9 %. Their low range of maximum dry density and optimum moisture content in the incompetent areas show that the soils have low bearing capacities. It equally makes them unqualified for any load to be imposed on them except they are improved upon using any of the soil stabilization techniques. Clay have the ability of failure if any load is imposed on it but soils that are mainly sand and gravel do not have that problem.